A comparative analysis of municipal public innovation: Evidence from Romania and United States - Anamaria Vrabie; Rodica Ianole-Călin (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
This paper aims to investigate innovation capacity mechanisms at a municipal level, through a comparative case study of public sector innovation labs from Boston (US) and Cluj-Napoca (Romania). We employed a qualitative approach, using as a primary tool the OECD framework for assessing the capacity of cities to innovate, and secondarily, a taxonomy of behavioral change strategies. We showed that, despite differences rooted in culture and institutions, innovation labs support the determinants of urban innovation capacity. However, the intensity of their support varies significantly, depending on organizational arrangements and the chosen methodological approach. Accepting this limitation may be an important step in re-configurating innovation labs and in moving towards a clearer agenda on sustainable urban innovation.
Keywords: 650; public sector innovation labs; innovation capacity; urban innovation; behavioral insights